Subxiphoid single-port video-assisted thoracoscopic surgery - Liu, Chia-Chuan (J Vis Surg, 2016)
BACKGROUND: We report the feasibility and safety of chest surgery through the subxiphoid single port approach based on our preliminary experience. METHODS: From December 2013 till January 2016, 39 patients underwent 40 thoracoscopic surgeries via a 3- to 4-cm subxiphoid single incision. A sternal lifter was applied for better entrance and working angle. A zero-degree deflectable scope was preferred. The technique for anatomic resection was similar to that in the traditional single-port approach. Patient characteristics and demographic data were analyzed. RESULTS: There were 29 females and 10 males, with a median age of 56 years. Indication for surgery included 24 patients with primary lung cancer, eight with lung metastases, two with benign lung lesions, one with bilateral pneumothorax, and five with mediastinal tumors. Surgeries included lobectomy in 21, segmentectomy in five, wedge resection in nine, and mediastinal surgery in five patients. There was no surgical mortality. Complications (10%, 4 in 40) included postoperative bleeding in one patient, chylothorax in one patient, and transient arrhythmia in the early learning curve in two patients. CONCLUSIONS: Our results indicated that subxiphoid single-incision thoracoscopic pulmonary resection could be performed safely but under careful patient selection with modification of instruments. Moreover, having a previous single-port incision experience was crucial. Major limitations of this approach included more frequently encountered instrument fighting; interference of left-side procedure related to heartbeat and radical mediastinal lymph node (LN) dissection; and the ability to handle complex conditions, such as anthracotic LNs, diffuse adhesion, and major bleeding.